LASIK To Improve Visual Acuity in Adult Neglected Refractive Amblyopic Eyes: Is It Worth? - Ali M. El-Ghatit; Adnan H. Marzouki (Journal of King Abdulaziz University: Medical Sciences, 2023)
The objective of this study is to establish if the correction of the refractive error with LASIK could lead to an improvement in adult neglected refractive amblyopia. A retrospective review of patients that underwent LASIK for the correction of adult refractive amblyopia was studied. Fourteen eyes were myopic, 3 eyes were hypermetrope and one eye was mixed astigmatic. Nine patients gained one or two lines (50%) all were from the myopic group, eight patients did not show any change (44.4%), and one patient lost one line (5.5%) and was astigmatic hypermetrope. A positive correlation was found between the pre and post operative; best corrected visual acuity between the improvement and satisfaction of the patients; between the degree of pre operative refractive error and the improvement in the best corrected visual acuity as well as between the pre and post operative refractive error. Adult patient with amblyopic eye can enjoy better vision after the procedure. In fact, refractive surgery for adult wishing to correct their neglect amblyopic eye previously thought to be refractory to visual rehabilitation may be considered.